KAJIAN PENGEMBANGAN USAHA BUDIDAYA IKAN AIR TAWAR DALAM MINA PADI DI DESA A. WIDODO KECAMATAN TUGUMULYO KABUPATEN MUSI RAWAS - Nuryasri, Salfiani; Badrudin, Redy; Suryanti, Melli (Jurnal AGRISEP, 2015)
This research is aimed at estimating the income of mina paddy farmers, identifying the criteria used to develop business, formulating the alternative development business. The data are analyzed by using income analysis and Analysis Hierarchy Process (AHP). The results of the research show that there are three types of fish applied in mina paddy: catfish, tilapia, and goldfish. The income of catfish in mina paddy amounting to Rp. 51.440.607,27,-/year, tilapia amounting to Rp. 35.895.335,- /year, goldfish in mina paddy amounting to Rp. 37.731.957,-/year. While from AHP analysis results, the criterias making an assessment in the development of aquaculture are production, revenues, marketing and third-party support. The highest value weighting results that become an alternative strategy to the development of aquaculture in mina paddy using software Expert Choice 11 is the application of catfish in mina paddy with weights value of 0,493.